(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Minimizing the complications of polychemotherapy, choosing the optimal treatment tactics in the treatment of oncological patients is one of the most urgent issues in the world. Chemotherapy is associated with the risk of developing nephrotoxicity, which can be manifested by acute tubular damage, acute tubulointerstitial nephritis, glomerular damage.